Формальні методи розпаралелювання алгоритму Тар'яна - Погорілий, С.Д.; Лозицький, С.І. (Видавничий дім "Академперіодика" НАН України, 2008)
We present a method for optimization of Tarjan’s algorithm for the detection of strongly connected components in a direct graph. The approach to its parallel implementation is offered, and the theoretical synthesis of the respective formula of the algorithm is formulated in systems of the modified algorithmic algebras of V.M. Glushkov. The theoretical estimations of increasing the productivity of the algorithm are obtained. These estimations have been checked up and confirmed in the experiment.